Scratching beneath the surface: how organisational culture influences curricular reform - Shah, Adarsh P. (2023)
Curricular reform is often proposed as the means to improve medical education and training. However, reform itself may not lead to noticeable change, possibly because the influence of organisational culture on change is given insufficient attention. We used a national reform of early-years surgical training as a natural opportunity to examine the interplay between organisational culture and change in surgical education. Our specific research question was: in what ways did organisational culture influence the implementation of Improving Surgical Training (IST)?